(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Optimum use of resources in crop production is crucial for reducing production costs and getting higher profits. Lentil farmers are traditionally using different inputs without considering their efficient use levels. Hence, the present study estimated the productivities of various lentil varieties and measured the resource use efficiency in lentil production. The study analyzed 360 household data collected from 240 improved variety users and 120 local cultivar users spread in the six lentil growing districts namely Faridpur, Magura, Kushtia, Jhenaidah, Manikgonj, and Sirajganj. Along with descriptive statistics, the study used Cobb- Douglas production and resource use efficiency models for analyzing the data. The average productivity of improved variety (1.63 t/ha) was much higher than local cultivars (1.08 t/ha). The highest productivity was found in mediumintensive growing areas due to the use of better variety (BARI lentil 8) and a higher level of inputs. Human labour, seed, TSP, MoP, other fertilizers, pesticides, irrigation, and variety had a positive and significant effect on lentil production. Farmers were not efficient in using inputs, they used excessive amount of labour but less amounts of seed and fertilizers. Lentil farmers faced the lack of suitable land, biotic and abiotic stresses, and lack of improved seeds. Farmers should be supplied with improved variety and production technology to increase farm profits through the efficient use of resources in lentil production. Bangladesh J. Agril. Res. 46(3): 231-243, September 2021